Penyuluhan dan Pelatihan Foto Produk dalam Meningkatkan Pemasaran UMKM di Desa Bandung Kecamatan Banjar Kabupaten Pandeglang Banten Indonesia - Irfan Faozi; Wintari Wintari; Rahmad Siva Maulana Ikhsan; Agus Sukirno (Lembaga Pengembangan Kinerja Dosen, 2024)
This activity is to improve the skills of micro, small and medium enterprises (MSMEs) in product photo documentation, as well as their skills in editing product photos for online marketing purposes. MSMEs are expected to be able to publish product photos that are well documented and have high publication value. Product photos can visually represent the unique attributes of an entity, such as its shape, philosophy and color, to characterize the entity. This entity can be an institution, company, product, or something similar. Typically, a photo has an underlying ideology that is used to depict a product. Usually, a photo has a different idea and concept that differentiates it from other brands. The product photo optimization training activity received several requests from participants aimed at increasing MSME business marketing efforts through social media. Therefore, partners must develop program activity strategies that can meet the specific needs of MSME players, especially those who have not yet fully used social media to optimize their product photos